In vitro Impact of Yeast Expressed Hybrid Peptide CATH-2TP5 as a Prophylactic Measure Toward Sepsis and Inflammation - Ahmad, Baseer; Hanif, Quratulain; Wei, Xubiao; Zhang, Lulu; Sabir, Naveed; Li, Zhongxuan; Cheng, Junhao; Khan, Shahzad Akbar; Basit, Abdul; Shahid, Muhammad; Rehman, Amin ur; Si, Dayong; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
CATH-2TP5 is a linear cationic hybrid peptide, consequent from naturally occurring antimicrobial peptide (AMPs) Cathelicidin-2 (CATH-2) and Immunomodulatory peptide Thymopentin (TP5) having dynamic and potent anti-inflammatory activities without hemolytic effect. The biocompatible mechanism of CATH-2TP5 is favored to explore new methodologies in the direction of biomedical applications. In this retrospectively study, an antiendotoxin and anti-inflammatory hybrid peptide CATH-2TP5 was emulated into pPICZα-A and successfully expressed in Pichia pastoris (P. pastoris). The recombinant CATH-2TP5 was purified through the Ni-affinity column and reversed-phase HPLC. The purified CATH-2TP5 peptide exhibited robust anti-endotoxin activity and significantly (p < 0.05) neutralized the effect of lipopolysaccharide (LPS). Furthermore, the down-regulated effect of CATH-2TP was more pronounced (p < 0.05) on LPS-induced cytotoxic effects, nitric oxide secretion and pro-inflammatory cytokines (TNF-α, IL-6, and IL-1β) in murine RAW264.7 macrophages. As associated to control and parental peptide the number of apoptotic cells was also contracted with the treatment of CATH-2TP5. Thus, we concluded that CATH-2TP5 peptide may be used in various biomedical applications as a therapeutic drug.